2014
DOI: 10.1080/14786419.2014.931392
|View full text |Cite
|
Sign up to set email alerts
|

Investigation of diversity inAegilops biuncialisandAegilops umbellulataby A-PAGE

Abstract: Aegilops species, wild relatives of wheat, are one of the important genetic resources in wheat breeding. In this study 13 populations of Aegilops biuncialis along with 2 populations of progenitor species Aegilops umbellulata were analysed in six replications using of acid polyacrylamide gel electrophoresis. The results showed that TN-01-293 population had a high gluten and grind quality because of high percentage of γ-45.31 and γ-43.5 (high gluten quality index) in the observed band. Also, Ahar population from… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 23 publications
0
3
0
Order By: Relevance
“…geniculata was reported by Medouri et al (2015) , who identified a total of 27 alleles at the two HMW glutenin loci, Glu-M1 and Glu-U1 , resulting in 29 HMW glutenin protein patterns. Other studies on the composition of glutenins and gliadins in Aegilops species have also been reported ( Bandou et al, 2009 ; Kozub et al, 2011 ; Wang et al, 2012 , 2015 ; Ahmadpoor et al, 2014 ; Dai et al, 2015 ; Medouri et al, 2015 ; Garg et al, 2016 ).…”
Section: Introductionmentioning
confidence: 77%
See 1 more Smart Citation
“…geniculata was reported by Medouri et al (2015) , who identified a total of 27 alleles at the two HMW glutenin loci, Glu-M1 and Glu-U1 , resulting in 29 HMW glutenin protein patterns. Other studies on the composition of glutenins and gliadins in Aegilops species have also been reported ( Bandou et al, 2009 ; Kozub et al, 2011 ; Wang et al, 2012 , 2015 ; Ahmadpoor et al, 2014 ; Dai et al, 2015 ; Medouri et al, 2015 ; Garg et al, 2016 ).…”
Section: Introductionmentioning
confidence: 77%
“…No studies have yet been reported on the composition of DF in Aegilops species with the U and M genomes, but previous results on HMW glutenin subunit alleles showed wide variation within these species ( Ahmadpoor et al, 2014 ; Dai et al, 2015 ; Medouri et al, 2015 ; Wang et al, 2015 ; Garg et al, 2016 ). In order to determine the extent of variation in the amounts of protein, β-glucan, TOT-pentosan, and WE-pentosan in Ae.…”
Section: Resultsmentioning
confidence: 99%
“…biuncialis and Ae. umbellulata have been reported to possess high gluten quality indices due to gliadins (Ahmadpoor et al, 2014) (Table 3). Gliadins from Ae.…”
Section: Utilization Of Aegilops For Improvement Of End Product Qualimentioning
confidence: 99%